Understanding science teachers' implementations of integrated STEM curricular units through a phenomenological multiple case study - Emily A. Dare; Joshua A. Ellis; Gillian H. Roehrig (SpringerOpen, 2018)
Abstract Background Current reforms in K-12 STEM education call for integration between science, technology, engineering, and mathematics (STEM). Such integration of STEM disciplines at the K-12 level offers students an opportunity to experience learning in real-world, multidisciplinary contexts; however, there is little reported research about teachers' experiences in engaging in integrated STEM instruction. The purpose of this phenomenological multiple case study is to understand nine science teachers' first-time experiences in implementing integrated STEM curricular units in their middle school physical science classrooms. This study draws upon both classroom implementation data and teacher reflective interviews to illustrate different degrees of integrated STEM instruction and to understand teachers' challenges and successes with these varying approaches. Results Our results indicate three distinct cases of integration within our sample that represent low, medium, and high degrees of STEM integration throughout curriculum implementations. Interviews with teachers from each case revealed three themes that varied across teachers' experiences: the nature of integration, choosing between science and engineering, and student engagement and motivation. Teachers in all three cases were challenged to make explicit connections between science, engineering, and mathematics while simultaneously maintaining a motivating and engaging context for their students throughout their instruction. Further, it appears that the degree of STEM integration that occurs in instruction may be related to teachers' ability to make explicit connections between the disciplines. Conclusions The work presented here informs educational researchers, policy makers, and K-12 STEM educators that there are several challenges when it comes to implementing new STEM initiatives in K-12 education. Although this work is limited to middle school physical science teachers' experiences with first-time STEM instruction, many of the identified themes are not content-specific; therefore, this work may shed light on general struggles that are common to educators who are integrating across content disciplines for the first time.